ANALYSIS OF HISTORY LEARNING TEXTBOOK IN SCHOOL: IN A REVIEW OF MICHEL FOUCAULT'S POWER RELATIONS THEORY - Ruslan, Ahmad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
History is a branch of science that studies human life in the past with its different dynamics and developments. The role of history in school is to provide students with an understanding of the ways of thinking and the processes involved in studying past events and what is no less critical to internalizing national identity. Another form of historical writing in formal education is textbooks. History learning textbook has an important role. Textbooks, as one of the learning tools used in school, must present historical facts that are truly objective and not only contain the government's interests. The purpose of learning history is to give students historical awareness so they know their identity. Students must know their national identity as a whole, be free from doctrines that contain political tendencies, and be made to liberate their minds more broadly and liberate themselves to the complex and comprehensive construction of historical knowledge.